7+4(z-8)=3-3z

Simple and best practice solution for 7+4(z-8)=3-3z equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7+4(z-8)=3-3z equation:


Simplifying
7 + 4(z + -8) = 3 + -3z

Reorder the terms:
7 + 4(-8 + z) = 3 + -3z
7 + (-8 * 4 + z * 4) = 3 + -3z
7 + (-32 + 4z) = 3 + -3z

Combine like terms: 7 + -32 = -25
-25 + 4z = 3 + -3z

Solving
-25 + 4z = 3 + -3z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '3z' to each side of the equation.
-25 + 4z + 3z = 3 + -3z + 3z

Combine like terms: 4z + 3z = 7z
-25 + 7z = 3 + -3z + 3z

Combine like terms: -3z + 3z = 0
-25 + 7z = 3 + 0
-25 + 7z = 3

Add '25' to each side of the equation.
-25 + 25 + 7z = 3 + 25

Combine like terms: -25 + 25 = 0
0 + 7z = 3 + 25
7z = 3 + 25

Combine like terms: 3 + 25 = 28
7z = 28

Divide each side by '7'.
z = 4

Simplifying
z = 4

See similar equations:

| 3x-6=2x+15 | | x-10x+25=0 | | (4v-6)(1+v)=0 | | 99.08/100*40.65=x | | 8n=6-14 | | 5x-2-7x=4+x-1 | | -2x-1/16=-6x^2 | | 56=4h/7 | | X^4-12x^4+48x^2-64=0 | | -7w=-91 | | -22=-p | | 8t-20=6t+10 | | 15n^2+19n+6=10+2n | | 3x^2+10x+15=-4X | | 15n^2+19+6=10+2n | | 0.02*40.65=x | | (x-2)=36 | | -64+30m=-34 | | 40.65*x=1 | | 18w+25=205 | | x+0.25x=1 | | X^2+36y^2-16x-72y+64=0 | | 32-4x=4 | | 8k=3k+75 | | 8m^2+2m+4=7 | | 8m^2+2m-3=7 | | -t=85 | | 15y-6y=22 | | t^2/2+2t=1/4 | | 4z^2+9z/z | | -12+10-10= | | 2b+5=115 |

Equations solver categories